Long-Term Risk of Death From Heart Disease Among Breast Cancer Patients - Agha, Aya; Wang, Xi; Wang, Ming; Lehrer, Eric J.; Horn, Samantha R.; Rosenberg, Jennifer C.; Trifiletti, Daniel M.; Diaz, Roberto; Louie, Alexander V.; Zaorsky, Nicholas G. (Frontiers in Cardiovascular Medicine, 2022)
Background Most breast cancer patients die of non-cancer causes. The risk of death from heart disease, a leading cause of death, is unknown. The aim of this study is to characterize the long-term risk of fatal heart disease in breast cancer patients. Methods This retrospective study used the Surveillance, Epidemiology, and End Results (SEER) database. Standard mortality ratios (SMR) were calculated for breast cancer patients diagnosed from 1992 to 2014. Patients were stratified by receipt of radiotherapy and/or chemotherapy, disease laterality, and diagnosis era. Hazard ratios (HRs) and odds ratios (ORs) were calculated to compare the risk of death from heart disease among other breast cancer patients. Results There were 1,059,048 patients diagnosed with breast cancer from 1992 to 2014, of which 47,872 (4.6%) died from heart disease. The SMR for death from heart disease at 10+ years for patients who received only radiotherapy was 2.92 (95% CI 2.81–3.04, p < 0.001) and in patients who received only chemotherapy was 5.05 (95% CI 4.57–5.55, p < 0.001). There was no statistically significant difference in SMR for death from heart disease for left-sided vs. right-sided disease. At 10+ years, heart disease made up 28% of deaths from non-primary cancer. HRs and ORs showed that the risk of death from heart disease was highest in patients older than 70 years of age and with longer follow-up. Conclusion The risk of fatal heart disease was highest in older breast cancer patients with longer follow-up (i.e., >5–10 years) and who received chemotherapy. These patients should be referred to cardio-oncology clinics to mitigate this risk.